Natural dyeing : learn how to create colour and dye textiles naturally - Davey, Kathryn; Kilfeather, Doreen (London Hardie Grant Books (London), 2022)
A complete guide to modern dyeing with simple projects, techniques and troubleshooting. Natural Dyeing explores the versatility of plant-based dyes, from understanding, choosing and preparing your fiber for dyeing to foraging for your dyes and the different dyeing methods used.
Natural dyeing & its many benefits -- Equipment & consideration -- Understanding & choosing fiber -- The dyeing process -- Fiber & dye -- Dye-based projects.
Includes index.
110223
Keywords: Dyes and dyeing; Plants, Useful; Dyes and dyeing, Domestic; Dye plants; Dyes and dyeing -- Textile fibers; Crafts & Hobbies -- Dye; Crafts & Hobbies . -- Fiber Arts & Textiles; Textile arts; Handicrafts